An Analysis Of Solar Energy Potential As Energy Source In Bandar Selamat Village - Alfauzan, Alfauzan; Solly Aryza; Zuraidah Tharo (Sean Institute, 2024)
Solar energy is one of the renewable energy sources that has great potential to be developed, especially in efforts to achieve sustainable development goals. Bandar Selamat Village has geographical conditions that allow the use of solar energy as an alternative energy source. This study aims to analyze the potential of solar energy in Bandar Selamat Village and evaluate its feasibility as the main energy source. The research methodology includes a collecting data on sunlight intensity, incident angle, and cloud distribution in the area. The data is analyzed to determine the potential for solar energy that can be generated. In addition, this study also evaluates the efficiency of solar panels and energy storage systems that can be used in Bandar Selamat Village. An economic analysis was conducted to examine the initial investment costs, operating costs, and long-term economic benefits of implementing Solar Power Plants (PLTS). The results of the study show that Bandar Selamat Village has significant solar energy potential with fairly high sunlight intensity throughout the year. The efficiency of the solar panels used in the simulation also showed adequate results to support local energy needs. In terms of economy, although the initial investment costs are relatively high, long-term economic benefits such as savings in electricity costs and reductions in greenhouse gas emissions can provide substantial benefits to the local community. This paper described a study concludes that solar energy has great potential to be developed as the main energy source in Bandar Selamat Village. To realize this, adequate policy support is needed, as well as increased infrastructure and public awareness of the benefits of renewable energy. Thus, Bandar Selamat Village can be an example of the implementation of sustainable clean energy at the local level.